2016
DOI: 10.1002/jssc.201600896
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive study of the macropore and mesopore size distributions in polymer monoliths using complementary physical characterization techniques and liquid chromatography

Abstract: Poly(styrene-co-divinylbenzene) monolithic stationary phases with two different domain sizes were synthesized by a thermally initiated free-radical copolymerization in capillary columns. The morphology was investigated at the meso- and macroscopic level using complementary physical characterization techniques aiming at better understanding the effect of column structure on separation performance. Varying the porogenic solvent ratio yielded materials with a mode pore size of 200 nm and 1.5 μm, respectively. Sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Meso-and macropores should be formed by different processes, and the measurements of meso-and macropores are based on radically different principles. 39 The tight correlation might be related to the photopolymerization procedure, but we report this merely as an incidential observation and will refrain from discussing this further here. Based on the macroporosity, the mesopore size distribution (cf.…”
Section:  Results and Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Meso-and macropores should be formed by different processes, and the measurements of meso-and macropores are based on radically different principles. 39 The tight correlation might be related to the photopolymerization procedure, but we report this merely as an incidential observation and will refrain from discussing this further here. Based on the macroporosity, the mesopore size distribution (cf.…”
Section:  Results and Discussionmentioning
confidence: 87%
“…A somewhat surprising observation is the tight correlation (Pearson r 2 = 0.9967) seen between the average mesopore size measured by nitrogen cryosorption and the median macropore size measured by mercury intrusion porosimetry (Figure S-2), in spite of a difference in size between these pore families of nearly 100 times. Meso- and macropores should be formed by different processes, and the measurements of meso- and macropores are based on radically different principles . The tight correlation might be related to the photopolymerization procedure, but we report this merely as an incidential observation and will refrain from discussing this further here.…”
Section: Resultsmentioning
confidence: 89%
“…Wouters et al developed a protocol combining several complementary physical characterization techniques (AFM, SEM, gas adsorption and mercury intrusion) to better understand the effect mesoand macroscopic morphology and its dependency on the polymer synthesis mixture. (101) They found that, although small-domain-size monoliths feature a relatively narrow macropore-size distribution, their homogeneity is compromised by the presence of a small number of large macropores, which induces a significant eddy-dispersion contribution to band broadening.…”
Section: Polymer Monolithsmentioning
confidence: 99%
“…The packed columns with a long length and small particles are beneficial in increasing peak capacity, but such columns require state-of-the-art UHPLC and column-packing instrumentation with the pressure higher than 1200 bar. , Monolithic columns, with the advantages of good permeability due to the continuous flow-through pores, offer an alternative to preparing a long column with relatively low backpressure . Silica-based monoliths possess a unique macro-mesopore structure with the advantages of an adjustable pore size, a relatively homogeneous structure, , and a high column efficiency . Thus, they are widely used in peptide separation.…”
mentioning
confidence: 99%
“…5,6 Monolithic columns, with the advantages of good permeability due to the continuous flow-through pores, offer an alternative to preparing a long column with relatively low backpressure. 7 Silica-based monoliths possess a unique macro-mesopore structure with the advantages of an adjustable pore size, 8−10 a relatively homogeneous structure, 8,11 and a high column efficiency. 12 Thus, they are widely used in peptide separation.…”
mentioning
confidence: 99%